Conditions for access to the Pronaf Agroecology line in the Territory of Cantuquiriguaçu/PR - Stoffel, Janete (2020)
With the institution of the National Program to Strengthen Family Agriculture in 1995, financial resources for family agriculture had a previously non-existent access channel. Among the subprograms of Pronaf is the line focused on agroecology, instituted from the 2003/2004 harvest, which has low access. In this context, the article presented here results from a research that seeks to analyze limits and potentialities in the access of family farmers to the Pronaf Agroecology line in the Cantuquiriguaçu / PR Citizenship Territory. Exploratory descriptive instruments were used, through a case study collecting data with family farmers and agents of financial institutions, seeking to compare and compare the answers about the lack of access to the subprogram in the region. The results indicate that the family farmers interviewed have an interest in accessing the resources, but due to lack of knowledge, difficulties regarding the requirements, fears about indebtedness and interest rates, this does not happen. In the case of financial institutions what has been observed is that the line is not attractive in financial terms to be made available. Consequently, there is no clear understanding of how it works and there is a need for technical assistance to be more effective in instructing, guiding and assisting family farmers to submit viable projects to financial institutions. Overcoming these limits can be a means of harnessing the potential of agroecological production, so important and necessary for social, environmental and economic sustainability.